2019
DOI: 10.3748/wjg.v25.i39.6006
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and survival after surgery for pancreatic cancer with or without acute pancreatitis

Abstract: BACKGROUNDIn pancreatic cancer, acute pancreatitis (AP) is a serious morbidity, but its negative effect on long-term outcomes remains to be elucidated.AIMTo investigate the effects of AP on the tumor recurrence pattern of pancreatic ductal adenocarcinoma (PDAC) and tumor-specific survival.METHODSThe medical records of 219 patients with curative pancreatectomy for pancreatic cancer at the Pancreatic Surgery Center of West China Hospital from July 2012 to December 2016 were analyzed retrospectively. The severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…IPFD was also investigated in the setting of pancreatitis—a major risk factor for pancreatic cancer[ 13 , 24 - 27 ]. A cross-sectional study by Stuart et al [ 28 ] investigated 119 individuals after an attack of pancreatitis and 38 healthy volunteers.…”
Section: Excess Body Fatmentioning
confidence: 99%
“…IPFD was also investigated in the setting of pancreatitis—a major risk factor for pancreatic cancer[ 13 , 24 - 27 ]. A cross-sectional study by Stuart et al [ 28 ] investigated 119 individuals after an attack of pancreatitis and 38 healthy volunteers.…”
Section: Excess Body Fatmentioning
confidence: 99%
“…The late response was a case considered as a failure at 1 year despite negative CEH EUS; the tumor disappeared completely at 53-month follow-up. We postulate that it could be a delayed success related to the activated immune response associated with RFA [18][19][20][21][22][23][24][25][26]. Conversely, an 18-mm NET located in the body of the pancreas seemed to disappear at 1 year after the size decreased to 13 mm at 6 months.…”
Section: Discussionmentioning
confidence: 90%
“…Although these results regarding short-term efficacy are interesting, surgery remains the treatment of choice in the absence of longterm follow-up and randomized series. However, regarding the results of surgical resection of benign tumors like NETs, the mortality rates range from 3 % to 14 % and morbidity rates from 15 % to 30 % compared to no mortality and morbidity ranging from 3 % to 10 % with EUS-RFA [21,22].…”
mentioning
confidence: 99%
“…A recent study performed by Gong et al[ 30 ], suggesting that a shorter overall survival for pancreatic ductal adenocarcinoma who got a AP than those without a history of AP and the HR for mortality was 1.808 (95%CI: 1.241-2.632). Similarly, it has been reported that AP is an independent risk factor for recurrence of PC (OR = 4.13; 95%CI: 1.41-12.10) and AP is associated with a worse disease-free survival of patients with PC[ 31 ]. Therefore, even if AP did not show a stronger association of PC risk compared with chronic pancreatitis, the relationship between AP and PC risk should be taken seriously.…”
Section: Discussionmentioning
confidence: 93%